2022
DOI: 10.3390/w14030370
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of a Fish Guidance System for a River Water Intake

Abstract: This paper describes the experimental study of a behavioural barrier consisting of a bubble curtain placed near an ecological river water intake, aiming to assess the bubble curtain’s influence on the velocity field of water flowing in the water intake proximity. The scientific novelty is given by the water intake solution operating in tandem with the dedicated bubble curtain generator used for avoiding fish entrapment. The water intake solution used in the present research is based on a run-of-river intake wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…The experimental results concerning the water velocity variation on horizontal and vertical planes, previously measured with a Pitot-Prandtl tube, were reported in Cîrciumaru et al [21], along with the results related to the water flow rate captured by the intake and the airflow rate introduced through the porous hose.…”
Section: Figure 1 Ecological Water Intakementioning
confidence: 91%
“…The experimental results concerning the water velocity variation on horizontal and vertical planes, previously measured with a Pitot-Prandtl tube, were reported in Cîrciumaru et al [21], along with the results related to the water flow rate captured by the intake and the airflow rate introduced through the porous hose.…”
Section: Figure 1 Ecological Water Intakementioning
confidence: 91%
“…They necessitate carrying out laboratory experiments in order to establish the tolerance thresholds for each species [22]. Dissolved gas barriers are quasi-efficient as long as a certain concentration is obtained (e.g., approximately 1.5 mg/L DO [12,23]). Either purified nitrogen or carbon dioxide was injected into the water to determine the feasibility of a gas bubble curtain [24].…”
Section: Assessment and Analysis Of Behavioral Barriersmentioning
confidence: 99%
“…Turnpenny et al [35] and Jones et al [36] also demonstrated that combined behavioral barriers are more efficient than independent ones. Thus, the use of the Types of behavioral barriers and their characteristics [12].…”
Section: Assessment and Analysis Of Behavioral Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of behavioral barriers (bubble curtains, strobe lights, sound, electricity, magnetic fields, or changed direction and velocity of the water flow) is to deter fish from entering zones that may pose a threat to them. Compared to physical barriers, behavioral barriers are based on the natural behaviors of fish [27] and require their activity; therefore, the effectiveness of the barriers largely depends on the swimming ability of the fish.…”
Section: Introductionmentioning
confidence: 99%